2018
DOI: 10.1155/2018/7301314
|View full text |Cite
|
Sign up to set email alerts
|

ESA CCI Soil Moisture Assimilation in SWAT for Improved Hydrological Simulation in Upper Huai River Basin

Abstract: e assimilation of satellite soil moisture (SM) products with coarse resolution is promising in improving rainfall-runoff modeling, but it is largely impacted by the data assimilation (DA) strategy. is study performs the assimilation of a satellite soil moisture product from the European Space Agency (ESA) Climate Change Initiative (CCI) in a physically based semidistributed hydrological model (SWAT) in the upper Huai River basin in China, with the objective to improve its rainfall-runoff simulation. In this as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…The ESA CCI program provides daily soil moisture (CCI-SM) at 0.25 • spatial resolution for approximately the top few millimeters to centimeters of soil from 1978 to 2016. The daily CCI-SM product (v03.2) is produced at 0.25 • spatial resolution from the microwave retrieved surface soil moisture data and is merged from multiple sensors Liu et al, 2011Liu et al, , 2012Wagner et al, 2012; Wagner et al, 2013) satellites. In this product, the absolute soil moisture was rescaled against the 0.25 • land surface modeling soil moisture (GLDAS-NOAH, Rodell et al, 2004) using cumulative density function matching.…”
Section: Esa CCI Microwave Soil Moisturementioning
confidence: 99%
See 1 more Smart Citation
“…The ESA CCI program provides daily soil moisture (CCI-SM) at 0.25 • spatial resolution for approximately the top few millimeters to centimeters of soil from 1978 to 2016. The daily CCI-SM product (v03.2) is produced at 0.25 • spatial resolution from the microwave retrieved surface soil moisture data and is merged from multiple sensors Liu et al, 2011Liu et al, , 2012Wagner et al, 2012; Wagner et al, 2013) satellites. In this product, the absolute soil moisture was rescaled against the 0.25 • land surface modeling soil moisture (GLDAS-NOAH, Rodell et al, 2004) using cumulative density function matching.…”
Section: Esa CCI Microwave Soil Moisturementioning
confidence: 99%
“…In this study, we used the merged product of active and passive soil moisture data which showed better accuracy than either the passive or active data alone (Liu et al, 2011). To match the spatial resolution of our CLM3.5 setup, the original SM values were re-sampled and re-gridded to 0.0275 • using the first-order conservative interpolation method (Jones, 1999), which is based on the ratio of source cell area overlapped with the corresponding destination cell area.…”
Section: Esa CCI Microwave Soil Moisturementioning
confidence: 99%
“…This project provides the possibility for long‐term dynamic analysis of soil moisture (Hollmann et al., 2013). The ESA CCI soil moisture data products have been applied widely in China, with most studies focused on small‐scale quality assessment and drought assessment (An et al., 2016; Liu, Wang, & Liu, 2018; Yao et al., 2018; Zhang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…New approaches have been developed to facilitate the incorporation of remotely sensed data to support watershed scale studies [14]. Of particular promise are data assimilation (DA) techniques adopted from the atmospheric science community, which have been increasingly applied to watershed hydrology studies [15][16][17]. However, the improvements that can be potentially conferred by DA have limitations.…”
Section: Introductionmentioning
confidence: 99%